Contesting Criticality: Epistemological and Practical Contradictions in Critical Reflection - Stephen Brookfield (Adult Education Research Conference, 2000)
Being critical is not an unequivocal concept. It is, rather, a contested idea. How the terms critical or criticality are used reflects the ideologies of the users.